ANALISIS PERBANDINGAN STRUKTUR BETON DENGAN MUTU Fc’ 30 DAN Fc’ 35 PADA MODEL PERENCANAAN GEDUNG ORMAWA UNANTI - Yuniarti, Dini; Syahrul Fuad, Indra; Firda, Ani; Al Faritzie, Hariman (LATERAL: Jurnal Teknik Sipil, 2025)
This study will evaluate concrete buildings with grades Fc'30 and Fc'35 in the planning model for the student organization building at Tridinanti University. The observation and literature approach was the research methodology employed in this study. The literature review, data collecting, planned structure drawings, primary data, structural modeling, load analysis, structural analysis, and design control are the eight stages of this research Structural analysis in compliance with SNI 2847-2019, SNI 1726-2019, and SNI 1727-2020 utilizing the ETABS application version 21.1. According to the results of the structural design utilizing the Intermediate Moment Resisting Frame System (SRPMM), the reinforcement is of quality Fy = 420 MPa, and the concrete utilized has a quality of Fc' = 30 MPa and Fc' = 35 MPa. Beam B1, measuring 400 x 200 mm, received reinforcement in the form of 4D13 and 6D13 for support, and 7D13 for field reinforcement. The child beam, measuring 250 mm by 150 mm, is produced by using 2D13 field reinforcement and 2D13 support reinforcement. Columns measuring 450 mm by 450 mm were found to have 2D-120 stirrup reinforcement in addition to 8D22 and 8D24 main reinforcement. The beam's tensile axial force is 693.1914 kN, compressive axial force is 1154.677 kN, shear force is 946.2809 kN, beam support moment is 1130.7728 kN, and field moment is 1007, 1748 kN. These are the resulting shear force, axial force, and moment of force. In the meantime, the column field moment is 6599.6249 kN, the column support moment is 2486.1633 kN, the column shear force is 3955.943 kN, and the column tensile axial force is 1902.8033 kN.